(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article examines the phenological stages of development of Chinese corn varieties planted in the agroclimatic conditions of the Syrdarya region. The study analyzed the duration of seed germination, vegetative development, flowering, grain formation, and ripening. The influence of the climatic and soil conditions of the Syrdarya region on the growth of Chinese hybrids was also assessed. The results of the study are important for the selection of high-yielding and rapidly adaptable corn varieties in the region.